From viscera to Sons of Horus: reassessing canopic practices in the early first millennium BCE - Klein, S (2022)
The removal and treatment of the viscera through the mummification processes were an essential and characteristic element of ancient Egyptian funerary culture, traditionally associated with the preservation of the body for the afterlife. This understanding originates from Victorian interpretations of death and the body. Several recent studies have used anthropological concepts and frameworks to challenge these views and gain important new insights into mummification processes and ancient Egyptian mortuary practices more generally. Until now, evisceration and canopic practices have only been studied through a traditional framework—devaluing their importance in broader funerary practices as simply a necessary step towards preservation of the body. This thesis addresses this limitation by analysing canopic practices through an alternative interpretative framework and the study of conceptual and material perspectives.